PERENCANAAN STRATEGIS SI/TI MENGGUNAKAN FRAMEWORK WARD & PEPPARD: STUDI KASUS UNIVERSITAS PARAMADINA - Syalevi, Rahmad; Nazief, Bobby A.A; Barcah, Quintin K. D. (The Indonesian Journal of Computer Science, 2025)
Universitas Paramadina (UPM) requires information technology (IT) infrastructure and services aligned with its vision, mission, and business processes to support its educational and research missions. Challenges in managing IT services at UPM necessitate a strategic IS/IT plan. Ward & Peppard is the approach used in this study to build an IS/IT strategic plan aligned with UPM's strategic objectives. The business model canvas, value chain analysis, critical success factor, PESTEL, mcfarlan’s strategic grid, and Gartner technology trends are employed as supporting analytical instruments. Data is collected through interviews, direct observations, and reviews of relevant documentation. Using thematic analysis and open coding methods, this research designs an IS/IT strategic plan for UPM. The results include recommendations for 8 new applications and 17 updates to existing applications, 13 IT initiatives focusing on infrastructure adjustments, and 10 IS/IT management strategies covering policy development, governance structure, data management, and IT audits. This strategic roadmap is developed for the next five years to enhance UPM's added value and competitive advantage through optimized IT.